Industry 4.0: a systematic review of the impact of technological innovation on commercial logistics processes (LACCEI, 2024)
The aim of this article is to analyze the research trends published on the impact of technological innovation into the commercial logistics processes since 2012 to 2022. The methodology used was the literature review, so it was developed according to the qualitative approach of descriptive design. In addition, with the support of the PRISMA Statement, 31 research articles were selected to analyze and examine the research trends of Industry 4.0 regarding the use of technological devices, such as the case of RFID and its implementation in business operations. The results suggest that Information Technology Communications and the Internet of Things (IoT) are optimizing business operations as they continue to be employed as part of business models that impact the use of information technologies, as well as new technologies, such as RFID, to improve logistics operations within the supply chain.